Evolution and Challenges of Customer Relationship Management (CRM) Implementation in the Digital Economy: A Systematic Review - Purnama, Kusna Djati; Manalu, Gibson (Journal of Management and Informatics, 2024)
The evolution of the digital economy has significantly influenced Customer Relationship Management (CRM), reshaping business strategies across industries. This study explores the development and challenges of CRM implementation during 2010–2024, with a focus on its adoption by small and medium-sized enterprises (SMEs). Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, 36 scholarly articles were analyzed to identify trends, obstacles, and outcomes associated with CRM in the digital economy. Findings reveal a steady increase in CRM adoption, particularly among SMEs, driven by advancements in electronic CRM (E-CRM) systems and the COVID-19 pandemic’s acceleration of digital transformation. Empirical data highlights that over 60% of Indonesian SMEs adopting CRM experienced a 20% sales increase within a year. Moreover, CRM implementation has enhanced customer loyalty by 25% and reduced marketing costs by 10% in European markets. However, significant challenges persist, including high implementation costs, inadequate technological readiness, and rising cybersecurity threats. For instance, cyberattacks targeting CRM systems have decreased customer trust by up to 15%. The study concludes that while CRM significantly boosts operational efficiency, customer satisfaction, and business innovation, addressing implementation barriers is crucial for its broader adoption. It recommends enhanced government and institutional support to provide SMEs with access to CRM technologies and training. The findings underscore CRM's critical role in fostering competitive advantages and call for future research to examine its long-term impacts in developing economies.